1978
DOI: 10.1111/j.1442-9993.1978.tb01177.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of habitat components by small mammals in eastern Australia

Abstract: The effect of habitat • components (vegetation density at two levels, litter, logs and roads) on the distribution of small mammals was assessed in adjacent areas of native forest and Pinus taeda plantation in north-eastern New South Wales. Rattus fuscipes was associated with structural complexity in native forest but not in pine plantation where it was found on downslope areas. R. rattus was associated with windrows in the pine plantation, R. lutreolus with areas devoid of a shrub layer in the pine plantation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 25 publications
(28 reference statements)
6
62
1
Order By: Relevance
“…Eleven categories of microhabitat were used, nine described previously in Bray (1994). These features have been found to be important in determining the local abundance of many species of small mammals, including the present study species (Barnett et al 1978;Dickman and Woodside 1983;Wilson 1991). Microhabitat descriptions, and sampling methodologies, are given in Table 1.…”
Section: Microhabitat Utilizationmentioning
confidence: 93%
See 1 more Smart Citation
“…Eleven categories of microhabitat were used, nine described previously in Bray (1994). These features have been found to be important in determining the local abundance of many species of small mammals, including the present study species (Barnett et al 1978;Dickman and Woodside 1983;Wilson 1991). Microhabitat descriptions, and sampling methodologies, are given in Table 1.…”
Section: Microhabitat Utilizationmentioning
confidence: 93%
“…Barnett et al 1978;Gullan and Robinson 1980;Wilson et al 1986;Monamy 1995), and inferences about the effects of competition have been made at both the community level (Fox 1981(Fox , 1989 and for pairs of coexisting species (Leung 1994;Haering and Fox 1995;Luo et al 1998;Monamy and Fox 1999). Experimental removal studies have demonstrated further for one pair of species, the swamp rat Rattus lutreolus and eastern chestnut mouse Pseudomys gracilicaudatus, that competition is asymmetrical with the swamp rat restricting the smaller species to inferior microhabitats (Higgs and Fox 1993; see also Thompson and Fox 1993).…”
Section: Introductionmentioning
confidence: 95%
“…Some species, notably birds, may readily traverse gaps between patches of suitable habitat; but for many faunal species, even small habitat discontinuities may pose a distributional barrier, or a severe limitation to free movement (Savidge 1973, Oxley et al 1974, Barnett et al 1978, Campbell 1981, Mader 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that the richness, distribution and abundance of co-existing small mammal species are influenced by the availability of microhabitats that can be measured by specific habitat variables (eg M'Closkey and Fieldwick 1975, Barnett et al 1978, Porter and Dueser 1982, Kemper and Bell 1985, Fa et al 1992, Laurance 1994. Dueser and Shugart (1978) investigated small mammal microhabitats in more structural detail than other studies by measuring 29 habitat variables around all their forest trap sites.…”
Section: Introductionmentioning
confidence: 99%